Pengaruh Inflasi dan Pengeluaran terhadap Kemiskinan di Provinsi Jambi Tahun 2016-2018 - Cahyani, Dea Ayu; Erniawanti, Veni; Gunawan, Agung; Nengsih, Titin Agustin; Mubyarto, Novi (Universitas Batanghari Jambi, 2024)
This study analyzes the impact of inflation and govemment expenditure on poverty in Jambi Province during the period of 2016-2018. Using panel data and regression analysis, the study finds that simultaneously, inflation and govemment expenditure significantly affect poverty levels. However, individually, neither inflation nor govemment expenditure significantly impactpoverty ata 5% significance level. The model used has a coefficient of determination of 99.48%, indicating that the independent variables in this study can explain most of the variation in poverty levels. These results indicate that while the overall modelis is good, the individual effects of inflation and expenditure on poverty are not significant.